The Prince of Poets' lament for Al-Manfaluti and Hafez Ibrahim: A comparative study - Mohammed, Ayman Elbialy (Journal of Arabic Language Sciences and Literature, 2022)
Balances in Arabic literature are among the most important distinguishing elements between poets. A poet does not precede a poet or a writer over a writer except after scrutiny and scrutiny of the product presented to the recipient. If the two writers compete in one subject, the one who excelled in his style and eloquence rose, and the recipient felt with him the sincerity of feelings and the purity of conscience. There is no doubt that lamentation is among the poetic purposes in which the writer innovates, and honesty prevails over him from the beginning until the full unloading of the sad charge that dominates the poet. The poem's introduction, main theme and conclusion all share in spreading an atmosphere of sadness and pain over the parting of the lament, with each poet being separated from another in the way of expressing these sorrows and pains. And perhaps we find a poet lamenting close relatives or lovers, so he creates a lament and elevates it, but in the second he did not reach the same elevation. At that time, it is necessary to look at the poet’s style in both systems, and to explain the reasons for his superiority there and his regression here, for nothing but an attempt to touch the beauty of Arabic and its ability to mastery, color and form according to what was mentioned by the writer of thoughts and feelings. In this regard, we do not underestimate the value of some methods while appreciating and elevating the value of others, but we point to the superiority of some of them over others, and if this was the case, it would have been more informative, and if it was presented or delayed that would have been innovated and indicated what is intended. Thus, the splendor of Arabic is manifested in its ability to distinguish between its styles for one purpose and one poet, while retaining the luster and fragrance of each style. The study here deals with an aspect of poetic balances, which is the balance between two poems by one poet, one of the two poems lamenting the great writer Mustafa Lutfi Al-Manfaluti, and the second lamenting the Nile poet Hafez Ibrahim.The study focused on several aspects, relying on what could be similar places between the two epitaphs, especially that the auditor finds similarities to some extent in some respects, for example, the beginning of the two poems, as well as verses of wisdom that he did not neglect Look at both poems, and the poet appeared through that and others in a poetic suit that obsessed him, even in the depth of his psychological crisis, we find him dealing with the pain of separation in different forms and images, which outweigh each other.Although the two elegies are great writers, their lamentation by the Prince of Poets was a special literary aspect that must be relied upon, deeply contemplated and lived in. This is what we tried to stand by and explain its details and distinguish between Shawqi’s methods and depictions of both elegies.
Keywords: Lamentations of personalities; balances; the prince of poets; al-Manfaluti; Hafez Ibrahim